Legal Governance of Sustainable Government for Achieving the Sustainable Development Goals: A Bibliometric Analysis - Simon Saimima; Andy Fefta Wijaya; Endah Setyowati; Benny Hutahayan (Unissula, 2026)
This study maps the intellectual structure, thematic evolution, and knowledge production of sustainable government research related to the Sustainable Development Goals (SDGs), with particular attention to legal governance. Using a bibliometric and science-mapping approach, this study analyzes 347 English-language journal articles indexed in Scopus and published between 2016 and 2025. The analysis was conducted using Biblioshiny/Bibliometrix and VOSviewer to examine publication trends, citation impact, leading contributors, institutional and country networks, keyword co-occurrence, and thematic evolution. The findings show rapid growth in sustainable government research after 2020, indicating increasing academic attention to SDG-oriented governance. Earlier publications received higher citation impact, reflecting their foundational role in the development of the field. Knowledge production is concentrated in China, Indonesia, the Netherlands, the United States, and Australia, with substantial contributions from universities and sustainability research institutions in Asia and Europe. The thematic analysis identifies governance integration, SDGs, and climate change as prominent themes, while sustainability functions as a foundational theme connecting governance, accountability, policy implementation, and institutional capacity. Legal and regulatory dimensions emerge through themes related to governance, accountability, institutional frameworks, and policy implementation, indicating the importance of legal governance in translating SDG commitments into sustainable government practices. The study contributes to legal and governance scholarship by consolidating fragmented literature and identifying the evolving role of legal governance in SDG-oriented sustainable government research.